Identidade territorial: estraégias de design para valorização de Santo Ângelo - Tarouco, Fabricio Farias (Universidade do Vale do Rio dos Sinos, 2011)
In this present globalization time, every place has to compete with other places in order to ensure visibility and space in this world of consumers. Places are consumed in different ways by different people: tourists, investors, companies and also by consumers from derived products. Therefore, seeing the territory as a product beyond its physical materiality means gathering immaterial factors to constitute it as a system. Thus, the territory starts to be seen and above all experienced as a product to be consumed. Many cities have been building their images intending to promote themselves as an attractive and a differentiated destination such as, the city of Santo Ângelo. Everything considered, the aim of this work is to interpret the territory as a product/brand and identify through the strategic design methodology, the actions and strategies used by the city of Santo Ângelo for the creation and strengthening of its territorial identity.
Keywords: Design estratégico; Identidade territorial; Santo Ângelo; Strategic design; Territorial identity; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial